(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Patients with chronic obstructive pulmonary disease are also prone to exacerbation with progression of their disease, which often lead to hypercapnic respiratory failure. Noninvasive ventilation has shown to have good outcomes in terms of reduction in mortality, reduction in need for intubation and mechanical ventilation and decreased duration of stay in the hospital in patients with COPD Aims & objectives: To study the efficacy of Non Invasive Ventilation, to check demographic profile, to measure the serial arterial blood gas analysis and to monitor respiratory status in patients with acute exacerbation of chronic obstructive pulmonary disease. Material & methods: A total of 50 patients were included in this prospective cross-sectional study. Detail history, clinical examination was done. Arterial blood gas analysis and laboratory parameters were studied before and after non-invasive ventilation. Results: 86% of patients belonged to 46-75 years of age. 78% of patients were male. 78% of patients were addicted to tobacco in any form. Significant improvement was found in pH, pO2, pCO2 value in arterial blood gas analysis and SpO2 value after four hours of noninvasive ventilation. Conclusion: Noninvasive ventilation is well tolerated in patients with acute exacerbation of chronic obstructive pulmonary disease.